THE REALIZATION OF INTERPERSONAL MEANING OF SPOKEN TEXTS IN AN EFL INTERNATIONAL TEXTBOOK: A SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE - Elih Sutisna Yanto; Hikmah Pravitasari (Wiralodra English Journal, 2023)
Interpersonal metafunction is an important concept when describing interactions in terms of responding to the act of giving or demanding goods, services, or information (Halliday and Mathiessen (2004). This article examines interpersonal meanings realized in the mood and modality resources of an Interchange Series textbook—the fourth edition textbook used for Grade 3 or Intermediate students. The research u discourse analysis and Systemic Functional Linguistics (SFL) as the main theoretical framework, and the analysis used the mood element as a central resource for the realization of interpersonal meaning. The results show that among the 275 clauses in the 16 texts, declarative sentences dominate (146 or 53.09 percent). Interrogative clauses are much less common (64, or 23.27 percent). None of the texts, therefore, utilize any of the imperative clauses. Furthermore, the number of modalization used in the sixteen texts are probability (26 or 9.45%), usuality (10 or 3.64%), and obligation (9 or 3.27%). This research suggests that forthcoming language textbooks may include examples of interpersonal meaning in terms of speech functions as resources for interaction. The implication is that language teachers could explicitly and systematically teach students interpersonal grammar of exchange that deals with the semantics of speech functions and modality. Teachers and students should be able to critically question textbooks as socio-semiotic agents since interpersonal meaning grammar helps people learn to deconstruct or interactively create spoken texts.